The Potential, Structure, and Effectiveness of the Local Tax System in Strengthening Local Own-Source Revenue (PAD) in Kotabaru Regency - Hamid, Ismar; Rahman, Mizan Ikhlasul; Srihardjanti, Rurien; Hidayat, Rachmat; Hidayah, Sri; Arqam, Muh.; Baihakki, Fajar; Sabar, Wardihan (Bulletin of Economic Studies (BEST), 2025)
Local own-source revenue (PAD) represents a core component of regional fiscal capacity and an essential indicator of subnational fiscal sustainability. This study examines the potential, revenue structure, and performance of local taxes in strengthening the local fiscal capacity of Kotabaru Regency. The analysis is based on secondary data on local tax revenues for the 2020–2024 period obtained from the Regional Revenue Agency of Kotabaru Regency. The empirical approach combines an assessment of tax composition and sectoral contributions, an evaluation of revenue target achievement, and trend and medium-term projection analysis using a logarithmic specification. The findings reveal that the local tax revenue structure in Kotabaru Regency is highly concentrated in Street Lighting Tax, Non-Metal and Rock Mineral Tax, and the Land and Building Rights Acquisition Duty (BPHTB), indicating a strong sectoral dependence on energy and extractive activities. While aggregate tax performance appears relatively strong, with average realizations exceeding annual targets, considerable heterogeneity is observed across tax instruments. Service-based and locally embedded taxes exhibit comparatively weak performance, pointing to untapped local tax capacity. The logarithmic trend estimates suggest a deceleration in revenue growth, consistent with diminishing returns in mature tax bases. These results imply that future fiscal strengthening should prioritize potential-based revenue planning, administrative efficiency and compliance enhancement, and diversification of the local tax base to improve regional fiscal resilience.